2009
DOI: 10.1098/rspb.2008.1536
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interactions and range limits: the diverse roles of predation

Abstract: Interactions between natural enemies and their victims are a pervasive feature of the natural world. In this paper, we discuss trophic interactions as determinants of geographic range limits. Predators can directly limit ranges, or do so in conjunction with competition. Dispersal can at times permit a specialist predator to constrain the distribution of its prey-and thus itself-along a gradient. Conversely, we suggest that predators can also at times permit prey to have larger ranges than would be seen without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 51 publications
6
102
0
Order By: Relevance
“…Lately, however, theoretical models have suggested that biotic interactions may also be important in shaping range limits (Holt and Barfield, 2009a), and recent empirical research has suggested that the distribution of many European bird species may not be as strongly related to climate as previously thought (Beale et al, 2008a). This weaker than expected association with abiotic climate variables may be explained if biotic interactions are more important than previously thought.…”
Section: Application To the European Bird Atlas Datamentioning
confidence: 54%
See 1 more Smart Citation
“…Lately, however, theoretical models have suggested that biotic interactions may also be important in shaping range limits (Holt and Barfield, 2009a), and recent empirical research has suggested that the distribution of many European bird species may not be as strongly related to climate as previously thought (Beale et al, 2008a). This weaker than expected association with abiotic climate variables may be explained if biotic interactions are more important than previously thought.…”
Section: Application To the European Bird Atlas Datamentioning
confidence: 54%
“…Secondly, there is growing evidence to suggest that the importance of climate and abiotic variables has previously been overstated (e.g. Watts and Worner 2008) largely because processes like the biotic interactions included in our models have previously been neglected (Davis et al, 1998;Beale et al, 2008b;Holt and Barfield, 2009b;La Sorte et al, 2009). It would clearly be valuable to develop the methods further to include both continuous variables and binary variables in the same analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, while to some extent previously downplayed, the importance of natural enemies in limiting the geographic ranges of the species that they use is coming increasingly to the fore (Case et al 2005). This latter perspective is developed in this special issue in papers on the roles of predation in range limitation (Holt & Barfield 2009), and more specifically the effects of sterilizing diseases (Antonovics 2009). In both cases, apparently counter-intuitive patterns can result from species interactions, including that predation can under some circumstances permit prey species to have larger ranges than would be the case in the absence of predation.…”
Section: Abstract: Ecology; Evolution; Geographic Rangementioning
confidence: 99%
“…A substantial research effort has been devoted to understanding the processes that set species range limits [48 -50], and theory has demonstrated that both the ecological [51,52] and evolutionary [53] structure of a species's range can differ substantially depending upon whether the gradient influences reproduction, survival or amount of habitat available. The few studies that have, to date, considered the dynamics of species shifting their ranges across environmental gradients have incorporated extremely simplified representations of the landscape and of dispersal [46,54,55].…”
Section: Discussionmentioning
confidence: 99%